O papel do coordenador pedagógico na formação continuada dos professores por meio da observação de aula e feedback formativo - Tamassia, Silvana Aparecida Santana (2023)
This research aims to analyze the possibilities of classroom observation and feedback as training strategies, understanding the difficulties the pedagogical coordinator (PC) may encounter in watching teachers in the classroom, in their daily lives, and what strategies have been used to implement it successfully. In this way, it will be possible to map and disseminate these practices seeking to improve teaching and learning processes, especially in Primary Public Schools. Methodologically, it constitutes a qualitative research, with contributions from quantitative research, developed from the mixed method of data production and emphasizing triangulation and complementarity modalities (MOSCOSO, 2017). For this, we prepared a questionnaire answered by pedagogical coordinators from different Secretariats of Education in the five regions of Brazil. Furthermore, we conducted semi-structured interviews with selected respondents and teachers who worked in their schools. In addition, we carried out a bibliographical analysis identifying related research and several authors who collaborated to discuss classroom observation, such as Nóvoa (1992), Weffort (1996), Tardif (2005), Placco and Souza (2006), Almeida and Placco ( 2009), Marcelo (2009), Elmore (2010) City et al. (2014), Imbernón (2006, 2009, 2016), Reis (2011), Alarcão (2009, 2020), Fusari (2006, 2011), Vasconcellos (2014) Furlanetto and Sellani (2017), Donnelly (2018), Darling-Hammond and Bransford (2019), Ninin (2019), among others. The results showed that observing classes and subsequent feedback should not be a solo action from a single PC or school, and they have a greater range of continuity when they are part of a whole school system policy. The main benefit pointed out by the participants was the training and professional development provided through the reflections brought during the feedback, increasing the quality of the work developed and favoring greater learning for the students. We also identified some difficulties encountered by the PC for the implementation process in their schools, such as the lack of support from principals and leaders in the Secretariats of Education, the resistance of some teachers, the lack of security to carry out feedback, the lack of time management and planning of the PC's routine, and often not enough training to prepare the PC for the pedagogical follow-up. In the end, we indicate some critical aspects so that classroom observation can be implemented and used as a training strategy for teacher development, which we hope can contribute to other schools and pedagogical coordinators